Ferroptosis: Redox Imbalance and Hematological Tumorigenesis - Lan, Hongying; Gao, Yu; Zhao, Zhengyang; Mei, Ziqing; Wang, Feng (Frontiers in Oncology, 2022)
Ferroptosis is a novel characterized form of cell death featured with iron-dependent lipid peroxidation, which is distinct from any known programmed cell death in the biological processes and morphological characteristics. Recent evidence points out that ferroptosis is correlated with numerous metabolic pathways, including iron homeostasis, lipid metabolism, and redox homeostasis, associating with the occurrence and treatment of hematological malignancies, such as multiple myeloma, leukemia, and lymphoma. Nowadays, utilizing ferroptosis as the target to prevent and treat hematological malignancies has become an active and challenging topic of research, and the regulatory network and physiological function of ferroptosis also need to be further elucidated. This review will summarize the recent progress in the molecular regulation of ferroptosis and the physiological roles and therapeutic potential of ferroptosis as the target in hematological malignancies.